The impact of in-service professional development on the quality of teacher-child interactions in early education and care: A meta-analysis. (February 2020) - Egert, Franziska; Dederer, Verena; Fukkink, Ruben G.
Abstract: High-quality interactions between young children and teachers in early childhood education and care (ECEC) are the cornerstone of educational quality. International findings suggest that the quality of interactions that support emotions and classroom organization is at a medium to high level, but the quality of instructional support is at a lower level. Within the "Teaching Through Interactions" framework developed by Hamre and colleagues (2013), several efforts were made to evaluate and improve key teacher-child interactions through in-service training. Our review includes experimental studies that evaluate professional development using the Classroom Assessment Scoring System measures. The systematic literature search and coding of studies was carried out by two independent reviewers. Our review includes 15 recent studies with 18 treatments. The meta-analysis (random effect model) showed an overall statistically significant professional development effect of g = 0.39 (SE = .08), i.e. close to a medium-size effect. In addition, effect sizes were almost equal for interactions related to emotional support, classroom organization, and instructional support (g= 0.35, 0.30, and 0.43, respectively). The quality of experimental studies and professional development was at a high level (e.g., individual component, feedback, or modeling) and experimental findings were generally positive. Our meta-analysis indicates that high-quality in-service programs have the strength to improve teacher-child interactions and pedagogical quality across all three domains. Highlights: In-service training improved teacher-child interactions across quality domains. Successful programs included workshop, coursework, and individual support. Self-reflection was a key element to increase instructional interactions.